The Relationship Between Social Support and Student Engagement for School Counseling Programs in Elementary Schools - Nurkholis; Toto Santi Aji; Amanda Maharani; Khusnul Khotimah (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2026)
Student engagement is a central element of the learning experience in elementary education, reflecting students’ behavioral, cognitive, and emotional participation in classroom activities. Rather than developing in isolation, engagement emerges through the interaction between students’ individual characteristics and the social support available within their surrounding environment. This investigation addresses the relationship between social support and student engagement among elementary school students, as well as its relevance for the planning of needs-oriented guidance and counseling services. A quantitative survey approach was employed involving 100 students from grades IV to VI. Data were gathered through questionnaires and examined using a SEM-PLS approach with the support of SmartPLS 4. The analysis indicates that differences in students’ engagement levels are closely linked to the degree of social support they receive. These findings suggest that guidance and counseling services should adopt a collaborative approach involving families and the school environment to effectively strengthen student engagement.